2004
DOI: 10.1097/01.pec.0000125654.20443.33
|View full text |Cite
|
Sign up to set email alerts
|

Poisoning Prevention Education During Emergency Department Visits for Childhood Poisoning

Abstract: Emergency department personnel are missing a potentially important opportunity to provide poisoning prevention education to families of children at high risk for repeat occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 0 publications
0
28
0
1
Order By: Relevance
“…1 Anybody in vehicle was injured 58. 8 Air bags deployed 87. 6 Visible damage to car seat *While this is the minimum age and weight to have an infant forward-facing, the current AAP recommendation is that children remain rear-facing to keep infants facing backward as long as possible, up to the weight limit for convertible car seat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Anybody in vehicle was injured 58. 8 Air bags deployed 87. 6 Visible damage to car seat *While this is the minimum age and weight to have an infant forward-facing, the current AAP recommendation is that children remain rear-facing to keep infants facing backward as long as possible, up to the weight limit for convertible car seat.…”
Section: Resultsmentioning
confidence: 99%
“…2 In addition to providing standard instructions, many authors promote using the ''teachable moment'' in the ED, when patients and families may be more receptive to specific disease-or injury prevention information. [3][4][5][6][7] While there is evidence that the pediatric ED can be successfully used as a venue to disseminate information about home safety [8][9][10][11] and motor vehicle safety, 12,13 the majority of injured patients do not receive injury prevention information as part of their postcare instructions. 14 The American Academy of Pediatrics (AAP) is an important source of injury prevention information and guidance and has published extensive recommendations regarding child passenger safety (CPS).…”
mentioning
confidence: 99%
“…[19] We did not fi nd records indicating that the children received any post exposure counseling and that there was no follow-up description. Though there is limited evidence suggesting that nasogastric lavage is an effective treatment for patients with poisoning, a signifi cant number of patients who received such treatment should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] Other epidemiological studies of pediatric poisoning have demonstrated that the most common risk factors for poison exposure are young age and female gender, which are in agreement with our fi ndings. [11][12][13][14][15][16][17] Poisoning incidents can be categorized into intentional or unintentional types based on how they happened, but most of childhood poisonings are accidental in nature. In the current study, most episodes were unintentional similar to those reported by Paudyal et al [18] (unintentional poisoning 98.4%) and by authors from Taiwan province (77.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, health promotion and injury prevention discussions rarely occur in the ED. 12,13 Even when ED physicians do provide health promotion information or counselling upon discharge these interactions are usually brief. 14 When counselling and health promotion opportunities are prioritized, an ED visit can serve as a "teachable moment"-a time when the patient, having just suffered an injury, will be most likely to understand advice and consider behaviour change.…”
Section: Introductionmentioning
confidence: 99%